PENGARUH PEMBERDAYAAN KARYAWAN TERHADAP KEUNGGULAN BERSAING MELALUI INTEGRASI RANTAI PASOKAN PADA PERUSAHAAN MAKANAN DI SURABAYA - Kusnadi Lydia (Business Accounting Review, 2015)
This study aimed to examine the affect of employees’ empowerment to competitive advantage through supply chain integration as the intervening variable. The data used in this study were primary data by using questionnaires. The sampling method techniques used was purposive sampling with 90 respondents from 30 food industries located in Surabaya. The research data analysis technique used was Partial Least Square (PLS) to examine the hypothesis of the research. Based on the analysis, it was proved that there was a positive significant influence of employees’ empowerment to competitive advantage either directly or indirectly through supply chain integration.